Mirabegron 50 mg once‐daily for the treatment of symptoms of overactive bladder: An overview of efficacy and tolerability over 12 weeks and 1 year. (4th August 2014) - Chapple, Christopher R; Kaplan, Steven A; Mitcheson, David; Blauwet, Mary Beth; Huang, Moses; Siddiqui, Emad; Khullar, Vik
Abstract The aim of the present review article was to summarize the efficacy and tolerability for mirabegron 50 mg over 12 weeks and 1 year versus placebo (SCORPIO) or tolterodine ER 4 mg (SCORPIO and TAURUS). After a 2‐week placebo run‐in, adults with overactive bladder symptoms for ≥3 months were randomized if, during a 3‐day micturition diary period before baseline, they had an average of ≥8 micturitions/24 h and ≥3 urgency episodes. Efficacy end‐points were change from baseline to each study visit and final visit in incontinence, micturitions, volume voided/micturition, urgency incontinence, urgency (grades 3 or 4), level of urgency and nocturia. Additional secondary efficacy variables included patient‐reported outcomes. Safety variables included changes in treatment‐emergent adverse events and vital signs. For SCORPIO, statistically significant improvements from baseline in efficacy variables and patient‐reported outcomes were seen with mirabegron versus placebo from week 4, and were maintained over time. For TAURUS, numerical improvements in efficacy were evident from month 1, and were maintained throughout 12 months. Treatment‐emergent adverse events incidence was similar between groups, except for dry mouth, which was reported by fourfold (SCORPIO) and threefold (TAURUS) more patients taking tolterodine than mirabegron. Mirabegron 50 mg for 12 weeks was associated with statistically significant improvements in objective measures of efficacy and patient‐reported outcomes. At final visit, improvements with mirabegron 50 mg were statistically greater versus placebo. The efficacy profile of mirabegron 50 mg appears to be maintained over 12 months.